SYSTEMATIC ANALYSIS OF K-FELDSPAR 40AR/39AR STEP HEATING RESULTS: I. SIGNIFICANCE OF ACTIVATION ENERGY DETERMINATIONS - Lovera O.M.; Grove M.; Harrison T.M.; Mahon K.I. (My University, 1997)
To better understand the argon retention properties of basement K-feldspars, step-heating results for 115 specimens representing a wide range of temperature-time evolution from a diverse array of geologic environments have been systematically evaluated. In carrying out the measurements, we instituted nonconventional analysis routines including: (1) duplicate isothermal steps; (2) multiple isothermal steps at 1100°C to extract as much gas as possible prior to melting; and (3) temperature cycling. To maintain a self-consistent approach, we systematically applied a weighted least square regression to determine the activation energies (E) and log(D0/r02) values. Activation energies were found to define a normal distribution (46 ± 6 kcal/mol) spanning over 30 kcal/mol. Corresponding log(D0/r02) values (5 ± 3 s−1) were highly correlated with E, yielding a slope that reproduces the previously documented feldspar compensation relationship. Numerical analysis of this correlation permits us to rule out large systematic laboratory errors in our data. In applying the multiple diffusion domain (MDD) model, we observed general tendencies in the domain distribution of basement K-feldspars. For the majority of samples, most 39Ar resides in the larger domains. The smallest domains generally constitute <5% volume fraction of the sample and tend to plot ∼2 orders of magnitude above log (D0/r02) Alternatively, the largest domains constrained by 39Ar released below melting have log(D/r2) values that are typically ~3 orders of magnitude smaller than log(D0/r02).Systematic analysis of the database demonstrates that the diffusion behavior predicted by the MDD model prevails for virtually all samples. However, two kinds of anomalous degassing behavior were observed. The first appears to be due to our inability to isolate effects resulting from distributions characterized by very small domains while the second may result from inhomogeneous K-distributions. Although these phenomena are capable of producing a wide range of calculated diffusion parameters, close inspection reveals that important systematics of the K-feldspar results cannot be accounted for these factors and remain best explained by real intrasample differences in diffusion properties. Finally, while uncertainties in E determined from step-heating experiments can produce significant dispersion in calculated temperatures (∼10°C/kcal/mol), the overall form of the cooling history, usually the most important result for tectonic applications, is preserved.